2022
DOI: 10.1523/eneuro.0009-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Lasting Effects of Activating BDNF-Expressing PVH Neurons on Energy Balance

Abstract: Brain-derived neurotrophic factor (BDNF) and its receptor, tropomyosin receptor kinase B (TrkB), are implicit in causing obesity. Mutations that reduce BDNF and TrkB expression are associated with obesity in humans and mice. Recently, it was reported that Bdnf gene deletion in the neurons of the paraventricular hypothalamus (PVH) caused positive energy balance and severe obesity in the form of hyperphagia, impaired adaptive thermogenesis, and decreased energy expenditure. Thus, we hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…As expected, viral overexpression of BDNF in the PVH decreases body weight in male rats ( Erdos et al, 2015 ). Activation of BDNF-expressing neurons of the PVH using a chemogenetic approach leads to suppressed food intake in male and female mice in both a fed and fasted state ( Wu and Xu, 2022 ). The same manipulation also raises respiratory exchange ratio (RER), and oxygen consumption in both sexes ( Wu and Xu, 2022 ).…”
Section: Role Of Hypothalamic Brain-derived Neurotrophic Factor Signa...mentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, viral overexpression of BDNF in the PVH decreases body weight in male rats ( Erdos et al, 2015 ). Activation of BDNF-expressing neurons of the PVH using a chemogenetic approach leads to suppressed food intake in male and female mice in both a fed and fasted state ( Wu and Xu, 2022 ). The same manipulation also raises respiratory exchange ratio (RER), and oxygen consumption in both sexes ( Wu and Xu, 2022 ).…”
Section: Role Of Hypothalamic Brain-derived Neurotrophic Factor Signa...mentioning
confidence: 99%
“…On the other hand, viral overexpression of BDNF in the PVH in male rats increases locomotor activity ( Erdos et al, 2015 ). Chemogenetic activation of BDNF-expressing neurons in the PVH also leads to increased locomotion in both male and female mice ( Wu and Xu, 2022 ). Altogether, these data show BDNF signaling in the hypothalamus plays a critical sex- and stress-dependent role in the coordination of satiety and body weight maintenance in part by increasing psychomotor activity.…”
Section: Role Of Hypothalamic Brain-derived Neurotrophic Factor Signa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Deleting Bdnf from the PVH results in obesity due to increased food intake, reduced energy expenditure, and reduced locomotion (An et al ., 2015). While PVH neuronal activity is reduced during feeding (Xu et al , 2019), activation of PVH BDNF neurons results in weight loss (Wu & Xu, 2022). We recently found that RAI1 promotes Bdnf expression in the hypothalamus throughout life (Javed et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…l, Quantification of food intake of GtACR (n=6) and control mice (n=6). m, Comparison of the latency to approach the chow pellet in open and closed inhibition for GtACR mice 72…”
mentioning
confidence: 99%